2011
DOI: 10.1007/s10706-011-9473-2
|View full text |Cite
|
Sign up to set email alerts
|

Small-Strain Shear Modulus and Damping Ratio of Sand-Rubber and Gravel-Rubber Mixtures

Abstract: This study examines the small-strain dynamic properties of mixtures composed of sandy and gravelly soils with granulated tire rubber in terms of shear modulus (G O ), and damping ratio in shear (D min ). Torsional resonant column tests are performed on dry, dense specimens of soil-rubber mixtures in a range of soil to rubber particles size 5:1-1:10 and rubber content from 0 to 35% by mixture weight. The experimental results indicate that the response of the mixtures is significantly affected by the content of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
80
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 165 publications
(93 citation statements)
references
References 27 publications
9
80
1
3
Order By: Relevance
“…A similar behavior, this time regarding the stiffness and damping ratio, was observed by Pamukcu and Akbulut [15]. Feng and Sutter [11], and Anastasiadis et al [33] reported that when the waste tire content was increased in a given waste tire and sand mixture, this resulted in a decrease of stiffness and an increase of damping ratio of the mixture. Anastasiadis et al [33] also showed that these changes in the properties of the mixture occurred in a close-to-linear fashion when the waste tire ratio allowed to be changed in the range of medium to high strain level.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…A similar behavior, this time regarding the stiffness and damping ratio, was observed by Pamukcu and Akbulut [15]. Feng and Sutter [11], and Anastasiadis et al [33] reported that when the waste tire content was increased in a given waste tire and sand mixture, this resulted in a decrease of stiffness and an increase of damping ratio of the mixture. Anastasiadis et al [33] also showed that these changes in the properties of the mixture occurred in a close-to-linear fashion when the waste tire ratio allowed to be changed in the range of medium to high strain level.…”
Section: Introductionsupporting
confidence: 77%
“…Feng and Sutter [11], and Anastasiadis et al [33] reported that when the waste tire content was increased in a given waste tire and sand mixture, this resulted in a decrease of stiffness and an increase of damping ratio of the mixture. Anastasiadis et al [33] also showed that these changes in the properties of the mixture occurred in a close-to-linear fashion when the waste tire ratio allowed to be changed in the range of medium to high strain level. Later studies done on the waste tire mixtures regarding the influence of confinement time have suggested analytical relationships between shear modulus and damping ratio of the mixtures at various strain levels [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Some ranges of D r =D s have been reported in previous pieces of research such as D r =D s 0:25 [14], D r =D s 0:8 1:1 [15,16], D r =D s 4 [17], D r =D s 5 [18], D r =D s 10 [19,20], D r =D s 20 [7,10,21], D r =D s 100 [6], D r =D s >> 100 [4,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Table 5 As shown in Figure 8, it can be observed that D min of loess decreases linearly as confining stress increases in double logarithm coordinates. In comparison to the data of D min of sand published in [20,21], loess possesses higher values of D min under the same confining pressure. However, the data of D min of loess are much lower than that of cohesive soils with higher PI published in [19].…”
Section: Small-strain Shear Modulus G O (A) Effect Of Water Contentmentioning
confidence: 43%
“…LZL-6-U/R specimens, the difference of G 0 between undisturbed and reconstituted specimens is big, while the values of G 0 between the undisturbed and reconstituted specimen are very close in saturated state. (b) Effect of confining pressure The general trends of the effect of the mean effective confining stress σ′ m on the smallstrain damping ratio D min of Lanzhou loess are illustrated in Figure 8, where the representative experimental results of D min for sand and cohesive soils [19,20,21] are included in the same figure as well. Table 5 As shown in Figure 8, it can be observed that D min of loess decreases linearly as confining stress increases in double logarithm coordinates.…”
Section: Small-strain Shear Modulus G O (A) Effect Of Water Contentmentioning
confidence: 99%